2020
DOI: 10.1080/0361526x.2020.1860862
|View full text |Cite
|
Sign up to set email alerts
|

Digital Accessibility: Overcoming the Challenges of Managing Grey Literature in Jamaica: The Case of the University of the West Indies Mona Library

Abstract: Grey literature is of inestimable value, with the potential for significant contributions to further inquiry and practice especially in academia and national development. Researchers, students, lecturers and scientists, depend on these resources which are often the main sources of indigenous and firsthand information. The challenge is retrieval, since they lack meaningful bibliographic control. They are usually not peer-reviewed and sometimes are of poor quality because they often originate from technocrats, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…At the starting time of lockdown, it was difficult for students and faculty members to shift online academic activities [ 49 , 103 ], as it was reported in developing countries that most of the material was in hard form and it takes time to be shifted online [ 104 , 105 ]. Hence, the digitalization of library materials and online library services had been started after the closure of higher education institutions [ 59 , 61 , 106 ]. Furthermore, the study findings are similar to the findings of Jin [ 25 ], Perkins [ 107 ] and Weyant [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the starting time of lockdown, it was difficult for students and faculty members to shift online academic activities [ 49 , 103 ], as it was reported in developing countries that most of the material was in hard form and it takes time to be shifted online [ 104 , 105 ]. Hence, the digitalization of library materials and online library services had been started after the closure of higher education institutions [ 59 , 61 , 106 ]. Furthermore, the study findings are similar to the findings of Jin [ 25 ], Perkins [ 107 ] and Weyant [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…After shifting educational activities to online mode [ 18 ], students from rural and urban areas equally benefitted from the online libraries [ 50 , 59 , 60 ]. It is also revealed that electronic modes are equally available to the students, readers and scholars [ 61 ]. These adequate provision of services and facilities were due to modern technology in the times of pandemic [ 12 , 13 , 62 ].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similarly, the stud findings show that e-libraries provide online information through digital resources including audio, video, e-books, e-journals, reports, and CD/DVD 1,[35][36][37] . The study findings of Robinson et al 38 assert the digital accessibility and managing the challenges of grey literature in Jamaica. In the same way, Ruschoff 39 reveals the digital environment and challenges to access electronic resources through bibliographic techniques.…”
Section: Review Of Literaturementioning
confidence: 89%
“…The value of grey literature to national development is inestimable. It is therefore imperative that they should be readily available and accessible through a powerful independent system (Robinson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%